Object Use in Children with Autism: Building with Blocks from a Piagetian Perspective - Iannaccone, Antonio; Savarese, Giulia; Manzi, Federico (Frontiers in Education, 2018)
Aim: This study focused on the manipulation of objects by children with suspected autism spectrum disorder. The aim was to demonstrate how objects can be seen as active agents of interpersonal exchange in face-to-face interactions. Participants: Three children with suspected autism spectrum disorder (aged 18, 20, and 24 months) were selected as representative of the sensorimotor stage of development. Methods: Starting from Piaget’s classical approach to the sensorimotor and symbolic developmental stages, the study moved towarda socio-material interpretation in which some patterns of interaction involving object manipulation seem to create a space that supports adult-child communication. In videotaped observations of verbal and non-verbal signs during an (organized) free play session, each child manipulated seven small blocks of colored plastic in the presence of an adult. The observations were informed by a checklist of 14 items, including eye contact and building a tower of toy blocks (from section B of the CHAT (CHecklist for Autism in Toddlers) instrument. Results: Based on a broad Piagetian perspective and recent work in the field of socio-materiality, key observations included the following: 1) sensorimotor and realistic play was observed in all three children; 2) there were some intriguing indications that objects serve as concrete mediators in the intersubjective space between adult and child; 3) some of the children’s attention patterns were visibly mediated by the object. Discussion and conclusions: All three children exhibited a particular sequence of actions. First, they manipulated the blocks through active experimentation; second, there was an apparent pause, during which the children were in fact examining the blocks to determine how best to continue the interaction; and finally, the children monitored adult attention by means of eye contact or by restarting manipulation of the blocks. As this last step in the sequence indicated that the object became a mediator of reciprocal attention, this interpersonal process was labeled “attention mediated by object.”